PERAN GURU DALAM PELAKSANAAN BIMBINGAN BELAJAR SEBAGAI UPAYA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SD GMIT 023 RUILAK - Sifra Eunike Lauring; Senti Atakari, Silpa Maiko, Yesi Mata, Petrus Mau Tellu Dony, Imanuel Yosafat Hadi Manapa (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to explore the implementation of learning guidance at SD GMIT 023 Ruilak as an effort to improve students’ learning outcomes. Learning guidance at the elementary school level is an essential service that helps students overcome learning difficulties, develop independence, and foster motivation to study. This service is also expected to improve the quality of the learning process, especially in schools located in areas with limited educational facilities. This research uses a qualitative method with a descriptive approach. Data were collected through classroom observations, interviews with the fourth-grade homeroom teacher, and documentation of students’ learning progress records. The data analysis technique applied is qualitative descriptive analysis, which includes data reduction, data presentation, and conclusion drawing. The results show that the implementation of learning guidance at SD GMIT 023 Ruilak still faces various challenges, such as limited time, low parental involvement, and the need for a more optimal individual approach. However, teachers play a crucial role in identifying students’ learning difficulties and providing pedagogical and emotional support to help students succeed in their studies. This study is expected to serve as a basis for improving learning guidance programs in elementary schools to make them more effective.